Age-specific changes in the molecular phenotype of patients with moderate-to-severe atopic dermatitis - Zhou, Lisa; Leonard, Alexandra; Pavel, Ana B.; Malik, Kunal; Raja, Aishwarya; Glickman, Jacob; Estrada, Yeriel D.; Peng, Xiangyu; del Duca, Ester; Sanz-Cabanillas, Juan; Ruano, Juan; Xu, Hui; et al. (Journal of allergy and clinical immunology, 2019)
Atopic dermatitis (AD) shows differential clinical presentation in older compared with younger patients. Nevertheless, changes in the AD molecular profile with age are unknown. We sought to characterize age-related changes in the AD profile. We evaluated age-specific changes in lesional and nonlesional tissues and blood from patients with moderate-to-severe AD (n = 246) and age-matched control subjects (n = 71) using immunohistochemistry, quantitative real-time PCR, and Singulex in a cross-sectional study. Patients were analyzed by age group (18-40, 41-60, and ≥61 years). Although disease severity/SCORAD scores were similar across AD age groups (mean, approximately 60 years; P = .873), dendritic cell infiltrates (CD1b+ and FcεRI+, P < .05) decreased with age. TH2 measures (IL5, IL13, CCL13, CCL18, and CCL26) significantly decreased with age in patients with AD, despite increasing with age in control subjects. Consistent with TH2 axis decreases, serum IgE levels and eosinophil counts negatively correlated with age in patients with AD (r = −0.24 and r = −0.23, respectively; P < .05). TH22-secreted IL22 expression levels also decreased with age uniquely in patients with AD (P < .05). Expression of TH1-related (IFNG, IL12/23p40, STAT1, and CXCL9; P < .05 for CXCL9) and TH17-related (IL17A and IL20; P < .05 for IL20) markers increased with age in both patients with AD and control subjects. Expression of terminal differentiation measures significantly increased in older patients with AD (loricrin [LOR] and filaggrin [FLG], P < .05), whereas expression of S100As (S100A8, P < .01) and hyperplasia markers (epidermal thickness, keratin 16, and Ki67; P < .05 for keratin 16) decreased. Serum trends in AD mimicked skin findings, with TH2 downregulation (CCL26; r = −0.32, P < .1) and TH1 upregulation (IFN-γ; r = 0.48, P < .01) with age. The adult AD profile varies with age. Although TH1/TH17 skewing increases in both patients with AD and control subjects, patients with AD show unique decreases in TH2/TH22 polarization and normalization of epithelial abnormalities. Thus age-specific treatment approaches might be beneficial for AD.